A Comprehensive Swot Analysis of Jaringan Gas (Jargas) Expansion for Household and Small-Customer Segments: Evidence from Pt Perusahaan Gas Negara (Pgn) Tbk, Semarang Area - Yudha, Aji; Diandra, Amanda; Lestari, Lela; Djastuti, Indi (Faculty of Economics and Business | Universitas Diponegoro, 2025)
This study aims to analyze the expansion strategy of the natural gas network (Jargas) for the household and small-customer segments implemented by PT Perusahaan Gas Negara (PGN) Tbk, Semarang Area, using the SWOT analysis method. The Jargas program represents a strategic form of business expansion that supports national energy efficiency and reduces dependence on LPG. This research employs a qualitative descriptive approach with data collection techniques comprising observation, Focus Group Discussion (FGD), and documentation. The findings indicate that PGN possesses several strengths, including a stable gas supply, competitive pricing, and the availability of a responsive operational support team. However, key weaknesses include the mandatory collection of customer interest, also referred to as the gas subscription request form or Formulir Registrasi Berlangganan Gas (FRGB) prior to construction, as well as reliance on the presence of anchor industries. Opportunities that can be leveraged include collaboration with local vendors, expansion into new areas, and high public interest in alternative energy. Meanwhile, threats faced by the company include the dominance of subsidized LPG 3 kg, limited pipeline infrastructure, and potential competitors. By understanding these factors, PGN can formulate more targeted, adaptive, and efficient expansion strategies to enhance the coverage of natural gas services for communities in the Semarang region